In God's name: An investigation into the murder of Pope John Paul I - Yallop, David A. frey50 (Bantam Books New York, 1984)
When Pope John Paul I died 33 days after his reign had begun, it was already known that he had decided on startling changes that would affect the doctrine, finances and hierarchy of the Roman Catholic Church. No official death certificate has ever been issued. No autopsy was performed. The cause of death, referred to by the Vatican in the vague terms, "possibly related to myocardial infarction", in fact remains unknown. In this fully documented minute by minute account of John Paul I's last hours and the events that followed, David Yallop reveals how the intricate web of Vatican lies was fabricated and explores the motives and opportunities of the six powerful men who stood at the center of a deadly conspiracy.
Keywords: Albino Luciani - Pope John Paul I. -- 1912 -1978.; John Paul I, Pope. -- Rome, Italy. -- Roman Catholic Church. -- Murder - Conspiracy